The Studying of Brand Management Dimensions on Sport Brand Management (Case Study of Zagros Kermanshah Province) - Mohammad Saeid Kiani; Shahab Baharmi (Allameh Tabataba'i University Press, 2019)
Purpose: The purpose of this study was to investigate the dimensions of brand impact on sports, economic and professional experts, managers and experts in Kermanshah province. Method: This is a descriptive-survey research. The statistical population consisted of 120 experts, managers and experts in sport and economic in Kermanshah province who were selected by random sampling. In this study, 87 experts including experts, managers and experts in two fields of sport and economics completed a researcher-made questionnaire assessing the dimensions of sport brand effectiveness. The measurement tool was a questionnaire of sport brand management whose reliability and validity were tested for this research. The Cronbach's alpha value for all factors is 7 or higher, indicating the appropriateness of the questions posed to assess each of the dimensions affecting sport brand management. SPSS software version 20 was used for data analysis. The results of the tests showed that all four sectors (managerial, economic, cultural and social) influenced sport brand management. Results: Finally, the overall summary of the tests shows that social media management brand with a mean of 3.09 and cultural management factor with a mean of 1.82 have the highest and lowest priority in influencing sport brand, respectively. Conclusions: The research results show that the social sector of the brand has a higher priority and microeconomic and macroeconomic indicators should be recognized.